Penerapan Cost, Volume And Profit Analysis Sebagai Alat Bantu Perencanaan Laba Pada Pabrik Paving Wahyu Agung - Fena Ulfa Aulia (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2018)
The orientation of the profit-oriented company is the desired maximum profit achievement. Maximum profit desired by the company will not be easy to achieve without any profit planning. The existence of profit planning can help the company to know the amount of sales that must be met in order to achieve profit targets. One of the tools in profit planning is Cost Volume Profit Analysis. This research is a quantitative descriptive research conducted at WAHYU AGUNG paving factory which is engaged in paving industry located in Teja Barat Village, Central Hamlet of Pamekasan Regency. The type of data used in this study is quantitative data obtained by conducting direct observation and interviews. The analysis technique of this research consists of four steps: to know the contribution margin ratio, to determine the break event point of the company, to determine the profit to be achieved in the next period and to calculate the margin of safety of the company. The results of this study indicate that there is a contribution margin ratio of 38.12%. Break Event Point paving factory WAHYU AGUNG Rp 32.124.941,71 or 1.647 units / 33 meters paving . The target of profit to be achieved in November 2017 is 30% of the profit achieved in October 2017 so that the sales to be increased by 1,829.46 units / 33 meters paving from the sales rate in October 2017 with a margin of safety of 21.55%.